A multibit burst error detection and correction mechanism for application layer - Bhattacharjee, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
To enhance the correctness and robustness of received text information at the receiver end, we propose an error detection and correction mechanism that executes at the application layer. Basically the error checking bits are incorporated with the original information during transition at the network. The error positions are detected by these error checking bits and then corresponding errors are corrected accordingly. Generally, the data link layer performs the task of error detection and correction but it platform dependent. So we introduce such a mechanism which is totally platform independent and acts at the application layer. It is capable of detecting all the error position and correcting all the error bits while it is destroyed or corrupted during the transmission. The data link layer sometimes fails to detect and correct all the error bits which can be solved by our proposed mechanism. Â© 2014 IEEE.